Descriptions of New Species of Chespirito Ferreira, Keller & Branham (Coleoptera: Lampyridae: Chespiritoinae) and the First Record for the Subfamily in the United States - Ferreira, Vinicius S.; Keller, Oliver; Ivie, Michael A. (Zootaxa, 2022)
Three new species of Chespirito Ferreira, Keller and Branham 2020 are described from North America, including the first species from the United States: Chespirito milleri new species from Arizona, USA, Chespirito hintoni new species from Mexico state, Mexico and Chespirito costae new species from Morelo state, Mexico. An updated distribution map and key to males of Chespirito is provided along with illustrations of diagnostic characters of the newly described species.